Distributing Rights, Social Justice, and Managing Conflict of Ahmadis - Anthin Lathifah (Fakultas Syariah, 2022)
The freedom of religion recognized as one of a fundamental rights whether in The Indonesian Constitution or international human right principles. However, Ahmadiyya in Indonesia does not recognize as one of religions or belief registered in the national laws, although in its implementation it largely depends on the policy of the local government. This article aims to describe the distribution patterns of rights, social justice, and conflict management for the Ahmadis in Wonosobo. This article is the result of qualitative research with a sosiological and political approach. The data were obtained from interviews and related documents. The analysis used is a descriptive analysis. The results of the study indicates that the distribution of the right of religious freedom towards Ahmadiyya in Wonosobo are realized for four reasons: 1) The Government's commitment to distribute the right of religious freedom for all its citizens with the existence of a local regulation that regulates human rights, including the religious right; 2) Synergic role between the government and the community in managing religious rights; 3) the ability of community leaders and religious leaders to manage, negotiate and solve problems when there is a religious conflict in the community; 4) government and society use communicative and inclusive methods. Therefore the four patterns can be a model in managing religious rights for minorities.